2018
DOI: 10.1108/ijph-03-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Drug injection within prison in Kyrgyzstan: elevated HIV risk and implications for scaling up opioid agonist treatments

Abstract: Purpose: Within-prison drug injection (WPDI) is a particularly high HIV risk behavior, yet has not been examined in Central Asia. A unique opportunity in Kyrgyzstan where both methadone maintenance treatment (MMT) and needle/syringe programs (NSP) exist allowed further inquiry into this high risk environment. Methodology: A randomly selected, nationally representative sample of prisoners within six months of release in Kyrgyzstan completed biobehavioral surveys. Inquiry about drug injection focused on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 64 publications
(113 reference statements)
1
23
0
Order By: Relevance
“…The impetus for the qualitative study upon which we draw here for our case was a large implementation science study designed to inform the delivery of methadone treatment into Kyrgyz prisons. Survey research has indicated moderate to high levels of HIV (10%) and hepatitis C (50%) among prisoners, and significant proportions (35%) of prisoners with a history of injecting drugs (of whom 85% inject drugs while in prison), yet only a minority (11%) of these engaged in methadone treatment (Azbel et al 2018). In response, an implementation science project sought to trial a motivational intervention to encourage methadone treatment uptake, and a parallel qualitative study sought to investigate prisoner engagements with methadone treatment.…”
Section: Case Studymentioning
confidence: 99%
“…The impetus for the qualitative study upon which we draw here for our case was a large implementation science study designed to inform the delivery of methadone treatment into Kyrgyz prisons. Survey research has indicated moderate to high levels of HIV (10%) and hepatitis C (50%) among prisoners, and significant proportions (35%) of prisoners with a history of injecting drugs (of whom 85% inject drugs while in prison), yet only a minority (11%) of these engaged in methadone treatment (Azbel et al 2018). In response, an implementation science project sought to trial a motivational intervention to encourage methadone treatment uptake, and a parallel qualitative study sought to investigate prisoner engagements with methadone treatment.…”
Section: Case Studymentioning
confidence: 99%
“…The parent project was designed to longitudinally and qualitatively assess barriers to MMT uptake during and after incarceration and evaluate the ways in which the prison risk environment influenced perceptions and use of methadone. Findings on HIV risk [ 24 ] suggest that most PWID incarcerated in Kyrgyzstan continue to inject in prison [ 6 ], prisoners are organized into rigid hierarchies that perpetuate inequalities in access to HIV prevention resources [ 23 ], and social factors shape patient engagement with methadone [ 22 ], especially after prison release and during the transition to communities [ 25 ] and among women [ 26 ]. Here, we explore the harmful health effects of Dimedrol injecting in prisons and implications for harm reduction programs.…”
Section: Methodsmentioning
confidence: 99%
“…Criminalization of drug use in EECA countries has concentrated people with HIV and substance use disorders (SUDs) into jails and prisons. Kyrgyzstan (Kyrgyz Republic) is an EECA country of six million people with high HIV prevalence (11.3%) among prisoners and detainees [ 3 ], most of whom (95%) are male [ 4 ] and one-third of whom are PWID [ 5 , 6 ]. From 2000 to 2018, Kyrgyzstan’s prison population declined by half, from 20,000 to approximately 10,000 detainees; however, seizures of illicit drugs and substance use within prisons increased during that same period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations